2021
DOI: 10.1037/pag0000627
|View full text |Cite
|
Sign up to set email alerts
|

Age-group differences in instructed emotion regulation effectiveness: A systematic review and meta-analysis.

Abstract: Several theories of emotional development in adulthood provide the rationale for anticipating enhanced emotion regulation effectiveness (i.e., successful, goal-consistent regulation of emotions) with age. However, the existing empirical evidence is ambiguous. The aims of the present systematic review and meta-analysis were to investigate age-group differences in instructed emotion regulation effectiveness, and to explore whether age-group differences in instructed emotion regulation effectiveness vary accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…This is inconsistent with lifespan theories suggesting that aging is associated with more effective emotion regulation (Charles, 2010; Urry & Gross, 2010) and with previous cross‐sectional studies finding that aging is associated with greater self‐reported emotion regulation effectiveness (Kessler & Staudinger, 2009; Phillips, Henry, Hosie & Milne, 2008). However, it is consistent with a recent meta‐analysis, showing no differences between young and older adults in performance‐based emotion regulation effectiveness assessed in experimental settings (Mikkelsen et al ., 2021). One explanation for this discrepancy in findings may be study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is inconsistent with lifespan theories suggesting that aging is associated with more effective emotion regulation (Charles, 2010; Urry & Gross, 2010) and with previous cross‐sectional studies finding that aging is associated with greater self‐reported emotion regulation effectiveness (Kessler & Staudinger, 2009; Phillips, Henry, Hosie & Milne, 2008). However, it is consistent with a recent meta‐analysis, showing no differences between young and older adults in performance‐based emotion regulation effectiveness assessed in experimental settings (Mikkelsen et al ., 2021). One explanation for this discrepancy in findings may be study design.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable amount of research on aging and emotion regulation has been conducted within the past decades (Allen & Windsor, 2019; Gurera & Isaacowitz, 2019; Helion, Krueger & Ochsner, 2019; Isaacowitz, 2022; Mikkelsen, Tramm & O'Toole, 2021). However, research specifically investigating the effect of age on emotion regulation effectiveness and emotion regulation dynamics in daily life is sparse (Isaacowitz, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Different ages may influence the correlation between mindfulness and emotion regulation. This age difference may be caused by psycho-social development factors and life goal selection factors [47]. On the one hand, with the continuous maturation of body and mind and the enrichment of interpersonal experience, individuals are more inclined to adopt conscious strategies to regulate emotions.…”
Section: Possible Moderating Variablementioning
confidence: 99%
“…Positive reappraisal was more effective for older adults whereas detached reappraisal was more effective for younger adults (Shiota & Levenson, 2009), although these results were not corroborated in a recent study (Livingstone & Isaacowitz, 2019). A meta-analysis of laboratory studies of emotion regulation found that effectiveness was largely stable in aging (Mikkelsen et al, 2021); similar results were found in a recent experience sampling study investigating the effectiveness of each family of regulation strategies in aging (Livingstone & Isaaowitz, 2021).…”
Section: Process Model Of Emotion Regulation: Research In Agingmentioning
confidence: 88%